A Market Development Business Strategy of Eco-Friendly Craft From Palm Oil Stand Waste in Rokan Hilir, Riau - Mardatillah, Annisa; Rosmayani, Rosmayani (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study aims to produce an analysis of the strategic position of the market development of the palm oil sticks waste craft industry and to determine an analysis of alternative strategies for the development of the palm-oil sticks waste craft market in Rokan Hilir Riau. This research method uses the QSPM (Quantitative Strategic Planning Matrix) method. The results of the QSPM analysis in this study to the formulation of alternative design strategies. Determine what, how, when, where and who runs QSPM. This study indicates that IFAS and EFAS are in the quadrant II position with coordinate values between 2.00 – 2.99. This position indicates that the palm-oil stick waste craft industry in Rokan Hilir Riau is positively strong. However, it faces significant challenges, so it must be managed with a market development strategy. While the results of the QSPM analysis show that the priority of alternative market development strategies is to increase the value of product uniqueness, product added value, knowledge capabilities, and craftsman skills. The industry is advised to increase its tactical strategy variations in demanding challenges. The business challenges are marketing, business network, technological innovation, and capital issues. The improvement of production facilities and infrastructure and increasing knowledge and skills of diversified processing artisans increase the unique value of the product and the added value of the product being more different than competitors. The research implications contribute to determining the market development strategy and theoretical implications related to the market development strategy concept. Keywords: business strategy, market development, QSPM, creative economy, ecofriendly